Determinants of aged cheese consumer preferences in Morocco—a cross-sectional study of economic, cultural, and social factors influencing purchasing behaviors - Nouhayla Mouatadid; Mourad Oukheda; Mourad Oukheda; Mustapha Khiati; Rachid Saile; Anass Kettani (Frontiers in Nutrition)
The shift in dietary habits, driven by increased exposure to global gastronomy and improved living standards, has led to a rise in the consumption of aged cheese, also known as matured cheese, worldwide. Although considered premium products, these cheeses transcend their culinary status to embody a cultural heritage, even in countries where this culture is not historically rooted, such as Morocco. However, this trend primarily affects consumption, while local production remains limited, reinforcing dependence on imports. In addition to their gastronomic dimension, these products are being increasingly promoted due to a growing awareness of their benefits, which is stimulating greater interest among consumers. This study aims to redefine the status of mature cheeses in Morocco by identifying the factors influencing their acceptability and consumer preferences. An online questionnaire, validated and distributed to a representative sample of the population, was used to statistically analyze these trends. The results reveal a promising market, characterized by strong interest in these products and frequent consumption, influenced by criteria related to the product’s characteristics and economic factors that shape the purchase decision, while the impact of sociodemographic variables remains more moderate. The acceptability of mature cheeses, particularly local products, is accompanied by a willingness on the part of consumers to favor quality over price, as well as a significant attachment to national production, which has been demonstrated. This dynamic opens up favorable prospects for the development of national production, reducing dependence on imports, and offering local producers an opportunity to strengthen their position in a market that remains relatively uncompetitive. A move upmarket, supported by a targeted marketing strategy that takes account of identified consumer disincentives and promotes the “local” character, would be an effective lever for boosting this sector, especially as the results indicate a marked appeal for these products.